2022
DOI: 10.3233/jad-220370
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Clinical Profiles of Apathy in Behavioral Variant Frontotemporal Dementia

Abstract: Background: Apathy is highly frequent in behavioral variant frontotemporal dementia (bvFTD). It is presumed to involve different pathophysiological mechanisms and neuroanatomical regions. Objective: We explored the hypothesis that subgroups showing distinct profiles of apathy and distinct patterns of atrophy within frontal lobes could be disentangled in bvFTD. Methods: Using data-driven clustering applied to 20 bvFTD patients, we isolated subgroups according to their profiles on the three subscales of the Dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This study was part of a larger-scale protocol that also collected other data that are reported elsewhere. 21,[23][24][25] Participants were recruited in the context of a clinical study at the Paris Brain Institute in France (Clinicaltrials.gov: NCT03272230). 21,[23][24][25] This clinical study aimed at assessing several behavioural symptoms (disinhibition and apathy) and investigating their neural correlates in behavioural variant frontotemporal dementia.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a larger-scale protocol that also collected other data that are reported elsewhere. 21,[23][24][25] Participants were recruited in the context of a clinical study at the Paris Brain Institute in France (Clinicaltrials.gov: NCT03272230). 21,[23][24][25] This clinical study aimed at assessing several behavioural symptoms (disinhibition and apathy) and investigating their neural correlates in behavioural variant frontotemporal dementia.…”
Section: Participantsmentioning
confidence: 99%
“…21,[23][24][25] Participants were recruited in the context of a clinical study at the Paris Brain Institute in France (Clinicaltrials.gov: NCT03272230). 21,[23][24][25] This clinical study aimed at assessing several behavioural symptoms (disinhibition and apathy) and investigating their neural correlates in behavioural variant frontotemporal dementia. BvFTD patients were recruited in two tertiary referral centres in Paris: the Pitié-Salpêtrière Hospital and the Lariboisière Fernand-Widal Hospital.…”
Section: Participantsmentioning
confidence: 99%
“…Behaviour modification strategies can be developed based on contingency management, where a person with bvFTD is rewarded with something they value after they have completed a certain activity of daily living (see a full description with examples in O’Connor et al 2016 [ 45 ]). When setting up interventions for bvFTD, understanding each individual’s cognitive and behavioural profile (e.g., apathy subtype) is pivotal to effective personalised care [ 46 , 47 ].…”
Section: Evidence-based Therapiesmentioning
confidence: 99%